Main drivers of natural gas prices in the Czech Republic: Market reform vs. long-term contracts - Monika Slabá; Petr Gapko (Charles University in Prague, Institute of Economic Studies (IES), 2011)
One of the goals of the European Commission in the energy sector is creating a single competitive European market. The decision of the European Union to liberalise energy markets has far-reaching consequences not only for gas companies, but also for the rest of the real economy in view of the fact that natural gas is being used as a primary energy source. In this paper we aim to answer how liberalisation has influenced gas pricing/prices in the Czech Republic and whether the liberalisation goals regarding prices have been fulfilled. Are they still coupled with light and heavy fuel oil and how, or are they decoupled and driven by the supply-demand relationship? Have they decreased? We investigate the individual components of end-customer gas prices according to the value-chain and we define and structure the drivers of these components. We pay extra attention to oil-linked pricing in long-term contracts and the consequences of market liberalisation/unbundling. We provide the reader with a case study from the Czech Republic, one of the Central and Eastern European countries, which, contrary to the old Member States, is buying most of its gas from one supplier (high import dependence, low supply diversity) and where the transmission and distribution network is characterised by a sufficient contractual and physical capacity. We stress that next to basic conditions on the European gas market (import dependency on external gas producers) individual legal and institutional conditions and the initial market structure of each Member State are also important for the results of the liberalisation process.
Keywords: D4; L95; L1; L43; G34; 330; gas prices; pricing; unbundling; liberalisation; long-term contracts; European Union; Czech Republic